Ertl surgery on the short fibula stump after war injury - Viktor Shevchuk; Yurii Bezsmertnyi; Olexander Bezsmertnyi; Olexander Branitsky (Medicinski glasnik, 2024)
Aim: To propose a new technique of Ertl-type surgery for significantly shortened and valgus deviated fibula stump. Methods: We present the case of a 26-year-old patient who underwent reamputation surgery to replace a significantly shortened fibula stump using a distraction regenerate formed after tibial stump osteotomy and dosed distraction of the autograft using the Ilizarov apparatus. Its advantage is the elimination of valgus deviation of the fibula remnant, its lengthening, formation of bone synostosis, and increase of the bearing surface, which provides the possibility of total contact prosthetics. Ra-diography, ultra-sound and MRI were used to monitor the regeneration. The observation period was 28 months. Results: Within 98 days after the operation, a regenerate was formed, replenishing the length of the fibula stump, the end of the fibula stump was consolidated with the re-generate, increasing the area of the bearing surface of the tibia stump by 2.5 times, which allowed for temporary and then permanent prosthetics. Conclusion: The proposed technique can be useful in reconstructive operations on the stump of the tibia.
Keywords: amputation; auto-grafts; osteotomy; synostosis; surgical; tibia